Comparison of Phytochemical, Proximate and Mineral Composition of Fresh and Dried Peppermint (Mentha piperita) Leaves - Mainasara, Muhammad Murtala; Abu Bakar, Mohd Fadzelly; Waziri, Ahmed Hassana; Musa, Amina Rabe (Journal of Science and Technology, 2018)
Mentha piperita well-known as peppermint is widely cultivated worldwide and used for its medicinal values. The purpose of this research was to evaluate fresh and dried M. piperita with the aim of quantifying chemical information, that might serve as a guide to exploit its potential and benefits for human nutrition. The phytochemical screening discovered that all of them possess flavonoids, saponins, alkaloids, tannins, steroid, glycosides and volatile oils. The proximate composition were determined according to the perspectives methods, while mineral elements were determined using EDTA method. Proximate analysis of both samples revealed that it contained 92.31% and 56.31% carbohydrates, 2.19% and 7.69% protein, 0.50% and 5% lipid, 1.5% and 9% fibre, 3.57% and 22%, ash, 89.5% and 9%, moisture respectively. The most predominant mineral found was potassium with a value of 72% and 23%, sodium 13% and 7.75%, and other minerals were found in low values ranging from calcium 0.5% and 0. 045%, magnesium 0.005% and 0.235%, and phosphorus 0.341% and 0.325%, respectively. This study contributes to the development of nutritional database of Â edible plants worldwide. In conclusion, fresh sample of M. piperita can be an excellent source of nutrients and antioxidant components.